Exploring the Nutritional and Nutraceutical Significance of Legumes: A Comparative Analysis Across Mashreq Countries - Nahla Hwalla; Ramia Al Bakain; Antonio Trani; Donato Mondelli; Biagio Di Terlizzi; Mouin Hamzé (New Medit)
This study investigates the nutritional and nutraceutical profiles of four legume species - bean, faba bean, chickpea, and lentil - collected from Lebanon, Syria, Jordan, Palestine, and Egypt. Chemical analyses assessed antioxidant, nutritional, and nutraceutical properties, followed by Principal Component Analysis and Hierarchical Cluster Analysis to examine similarities and differences among legume varieties and regions. Key findings include Lebanese beans with distinct tocopherol (vitamin E), polyphenols, flavonoids, and TEAC, along with high protein, lysine, and methionine. Syrian faba beans showed superior vitamin E, TEAC, protein, lysine, and methionine levels, while a Palestinian variety excelled in polyphenols and flavonoids. Syrian chickpeas were rich in vitamin E, flavonoids, protein, and methionine, and a Palestinian variety stood out for histidine and lysine. Lentils from Lebanon, Syria, and Palestine had notable vitamin E and methionine contents. These findings highlight the role of genetic, environmental, and geographical factors in legume quality, emphasizing their potential in addressing malnutrition and promoting sustainable food systems.